Attitudes toward xenotransplantation: A survey of parents and pediatric cardiac providers. (6th October 2020) - Padilla, Luz A.; Rhodes, Leslie; Sorabella, Robert A.; Hurst, Daniel J.; Cleveland, David C.; Dabal, Robert J.; Cooper, David K.; Paris, Wayne; Carlo, Waldemar F.
Abstract: Background: Scientific advancements are occurring in cardiac xenotransplantation (XTx). However, there have been religious and social concerns surrounding this allotransplantation alternative. The purpose of this study was to explore the acceptance of XTx among stakeholders of the congenital heart disease (CHD) community. Methods: A Likert‐scale anonymous survey was distributed to physicians and nurses who care for children with CHD and parents of children with CHD. Psychosocial and clinical attitudes were compared across all groups to identify differences, and regression analysis was performed to identify factors associated with XTx acceptance. Results: A total of 297 responded to the survey: 134 physicians, 62 nurses, and 101 parents. Potential acceptance of XTx if outcomes were similar to allotransplantation was high overall (75.3%), but different between the groups (physicians 86%; nurses 71%, parents 64%; P  < .0001). Regression analysis showed respondents who reported religion would influence medical decision making (OR 0.48; 95%CI 0.24‐0.97) and those who would not use a pig heart transplant as a bridge until a human heart became available were less likely to accept XTx (OR 0.09; 95%CI 0.04‐0.21). Psychosocial concerns to XTx were minimal but were also associated with XTx acceptance particularly among parents (OR 0.17; 95%CI 0.03‐0.80). Conclusions: Potential acceptance of XTx is high, assuming results are similar to allotransplantation. Religious beliefs and attitudes toward the use of XTx as a bridge to allotransplant may present barriers to XTx acceptance. Future research is needed to assess potential attitude differences in light of ethical, psychosocial, and religious objections to XTx.